Feasibility of Fast-Track Elements in Pediatric Surgery - Reismann, M.; Arar, M.; Hofmann, A.; Schukfeh, N.; Ure, B. (European Journal of Pediatric Surgery, 2012)
Background We recently showed that fast-track pathways could be applied to only one third of patients undergoing routine pediatric surgery. The aim of this study was to investigate various fast-track elements in various procedure types irrespective of the applicability of a whole fast-track pathway.Methods Patients undergoing routine surgical procedures from April 2009 to April 2010 were included in the study. 11 groups of procedures were differentiated and quality criteria were established for 8 fast-track elements: analgesia, postoperative nutrition, postoperative mobilization, applicability of minimally invasive surgery when appropriate, hospital stay, postoperative symptoms, complications, and parental evaluation. A fast-track element was considered as successfully applied if used in at least 75% of patients. The hospital stay was compared with data from the German reimbursement system (G-DRG).Results A total of 203 patients were included. Optimal analgesia was achieved in all procedure types except in oncologic surgery (58%) and ureteral reimplantation (71%). Significant nausea and vomiting occurred only after Kasai operation and “other laparoscopic procedures”. Early nutrition was achieved in all procedures except after fundoplication (67%) and Kasai operation (62%). Early postoperative mobilization was not successful after hypospadias repair (40%) and ureteral reimplantation (43%). Minimally invasive techniques could not be applied in 48% of thoracic procedures and in 58% of oncological patients. There were no fast-track associated complications. In 4 of 11 procedure types, the mean hospital stay was significantly reduced compared to G-DRG data. There were 4 readmissions (2%). 2 weeks after discharge 94% of interviewed parents evaluated fast-track treatment as excellent.Conclusion Fast-track elements in pediatric surgery increase patient comfort, reduce hospital stay, and achieve a high patient satisfaction. We wish to emphasize the benefits of using fast-track elements irrespective of whether a whole fast-track protocol is applicable.
Keywords: fast-track elements; feasibility; children